INTEGRATING APPRECIATIVE INQUIRY APPROACH IN TOURISM RESEARCH: WHY AND HOW IT SHOULD BE APPLIED? - Naqib Md Yunoh; Ida Nadia Hamidon, (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
This paper provides much scope to expand the literature by considering methods to apply the Appreciative Inquiry (AI) approach to tourism research. AI has been developed to gain and built enduring relationships between communities and the tourism industry based on the simple assumption that every organization or community has something that works well and that those strengths can be the starting point for creating positive change. AI approach also can be used to facilitate positive developments within organizations and that AI could be employed in this way within the tourism industry. Previous studies believed that the task of tourism development in rural areas, conservation of environment and livelihood improvement is only possible through the joint effort of a range of stakeholders that includes governments, tourism entrepreneurs, non-profit organizations, and local people. It is also applicable and an interesting approach as AI treats people as human beings, not machines. There are also limited studies that have been conducted using the AI approach within the tourism field. Thus, it is important for tourism practitioners to extend AI into the field of tourism to create a focus on the strengths of a system instead of using deficit-based thinking.